Peningkatan Hasil Belajar Siswa Pada Pelajaran PAI Melalui Model Pembelajaran Problem Based Learning (PBL) Pada Kelas XI C SMA Al Azhar Menganti Gresik - Moh Misbahul Munir (Jurnal Pendidikan Agama Islam Miazhar, 2025)
The background of this study is that there are still many students who do not pay attention to the teacher's explanation during the explanation process. Students tend to be passive when the learning process takes place, and the results of the even semester exams still have not reached the minimum completion criteria (KKM) expected, Therefore, researchers make improvements that require innovation of new learning models to stimulate students' interest in improving PAI learning outcomes. In this context, the Problem Based Learning learning model is used which is a teaching model with a student learning approach to authentic problems. The formulation of the problem in this study is 1) Can the application of the Problem Based Learning (PBL) model improve learning outcomes for the material of the branch of faith (syu'ab al-īmān), the relationship between faith, Islam, and ihsan? 2) How can the implementation of the Problem Based Learning (PBL) model improve learning outcomes for the material of the branch of faith (syu'ab al-īmān), the relationship between faith, Islam, and ihsan? This PTK was conducted in two cycles using a research model from Kurt Lewin's theory which has 4 stages, namely: Planning, Acting, Observing, and Reflecting. The method of data collection used test, observation, and documentation techniques. In the Pre-Cycle activities before the application of the Problem Based Learning (PBL) model in this study, an average class value of 79 was obtained with a percentage value of student learning completion of 51.4%, then in cycle I there was an increase in the average class value of 82 with a percentage value of learning completion of 60%. Then in cycle II there was another increase with an average class value of 86 and a percentage value of learning completion of 85.7% and included in the Very Good category. The application of the Problem Based Learning (PBL) learning model approach in this study obtained the results of teacher activity observations in cycle I of 2.75 increasing in cycle II of 3.25 And the acquisition of student observation results in cycle I obtained 57.8% in cycle II increasing to 93.7%. Based on the results obtained from the classroom action research that has been carried out, it can run well and is included in the Good category.